2006
DOI: 10.3892/ijo.28.6.1571
|View full text |Cite
|
Sign up to set email alerts
|

Primary bone lymphoma: A retrospective analysis

Abstract: The aim of this study was to retrospectively define those patients with unequivocal primary bone lymphoma presenting to the Sheffield Lymphoma Group and document patient and tumour characteristics and management strategies, and correlate these with survival. Thirty-seven patients were documented from a total of 3148 cases of non-Hodgkin's lymphoma seen over 34 years. There were 17 males and 20 females, with a mean age of 55.4 years (range, 27-78). Pain was the most commonly presented symptom (67.5%), and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
8
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 18 publications
(39 reference statements)
8
41
8
8
Order By: Relevance
“…Most studies had small patient numbers retrospectively collected over a long timespan, resulting in a heterogeneous group of patients with different staging methods and treatment approaches [3,5,6,8,9,13,15,16]. Any study on this subject needs to span years or even decades; Ostrowski et al's report covers 75 years [11].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies had small patient numbers retrospectively collected over a long timespan, resulting in a heterogeneous group of patients with different staging methods and treatment approaches [3,5,6,8,9,13,15,16]. Any study on this subject needs to span years or even decades; Ostrowski et al's report covers 75 years [11].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors report a similar prevalence, with DLBCL accounting for 73 % to >90 % [4-6, 12, 13, 16, 17]. Pathological fractures are reported in 10-21 % of patients [4,5,12,16], but a rate of 43 % was found in one series [9]. In our series, 28.6 % of patients suffered a pathological fracture.…”
Section: Discussionmentioning
confidence: 45%
“…1 A 23-year-old woman with primary bone lymphoma affecting the right proximal humerus: a coronal magnetic resonance imaging (MRI) view at presentation; b coronal MRI after chemotherapy and radiotherapy; c X-ray after chemotherapy and radiotherapy; d resection and reconstruction with prosthesis were performed Fig. 2 A 54-year-old man with primary bone lymphoma affecting the right tibia: a magnetic resonance imaging (MRI); b a few days after biopsy, a pathological fracture occurred; c before beginning chemotherapy and radiotherapy, the fracture was fixed with a plate without curettage of the involved bone; d fracture completely healed and the patient was disease free at 78 months Age seems to be an important factor in our series, as outlined previously by different authors [6,7,9,11,12,16], with younger age accounting for a better prognosis; however, in our series, there was only a trend for a better survival in younger patients, which did not reach statistical significance. The only positive prognostic factor found in our series was achievement of complete remission after primary treatment.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The five-year OS rates vary greatly, as demonstrated in clinical trials and retrospective population-based studies (2,9,20,28,29,51,53). In addition, various studies have suggested different prognostic factors, including age (29,50,51,56), gender (10), stage (2), LDH levels (10), lesion range (51) and IPI score (28,56). Considering these factors, the case reported in the present study may have a poor prognosis.…”
Section: Discussionmentioning
confidence: 89%